Pengaruh Abu Limbah Rak Telur Sebagai Substitusi Filler Dalam Campuran Laston AC-WC - James William Palayukan; Alpius; Charles Kamba (Paulus Civil Engineering Journal, 2022)
This study was intended to determine the characteristics of the mixture of worn-out concrete with the addition of egg rack ash as a substitute for cement filler in the mixture of worn-out concrete. The method in this research is to carry out a series of tests, namely testing the characteristics of egg tray ash where the characteristics of egg tray ash are checking the specific gravity of egg tray ash. Then designing the composition of the worn-out lastton mixture and Marshall testing to get the characteristics of the worn-out laston mixture with the addition of egg tray ash as a cement filler substitution, with a composition of 0%, 25%, 75%, and 100% egg tray ash content using General Specifications of Bina Marga 2018. At 0% and 25% egg tray ash content, the stability, flow, VIM, VMA, VFB values ​​met the specifications. At 50% ash content Stability, flow, VIM, VFB meet the specifications, while VMA does not meet. At 75% ash content and 100% stability value, VIM, VFB met the specifications, while flow and VMA did not meet the specifications. The characteristics of the worn layer Laston mixture with the substitution of egg tray ash filler with cement only at a 25% ash content that meets the General Specifications of Bina Marga 2018.